Looking beyond zoom fatigue: The relationship between video chatting and appearance satisfaction in men and women. Issue 7 (4th May 2022) - Harriger, Jennifer A.; Pfund, Gabrielle N.
Abstract: Objective: The COVID‐19 pandemic led to a transition to the utilization of video chatting services as the main form of communication for work, family, and friends. However, the repercussions of this change are not fully known, and issues regarding appearance satisfaction are particularly salient. The purpose of the current study was to examine the relationship between video chatting and appearance satisfaction in a sample of men and women. Method: The current study utilizes cross‐sectional data from 618 participants (Age: M = 33.2; 54.1% women) to evaluate whether average video chat usage predicts appearance satisfaction, and whether this association is dependent upon appearance comparison or self‐objectification. Results: Results indicated that individuals who spent more time video chatting reported higher appearance satisfaction. Additionally, appearance comparison and self‐objectification were not significant moderators, and the association between video chat usage and appearance satisfaction did not differ based on gender. Usage of the touch‐up feature, gallery view, and amount of time spent looking at oneself were associated with appearance comparisons, while adjusting lighting and camera angles and amount of time spent looking at oneself were associated with self‐objectification. Discussion: The results may indicate that while overall time spent video chatting may be associated with lower appearance concerns, examination of the usage of specific features on video chatting platforms may be important to assess in the future. Public Significance: This study demonstrates that overall time spent video chatting may be associated with lower appearance concerns. The usage, however, of specific features on video chatting platforms, such as touch‐up feature, gallery view, and amount of time spent looking at oneself were associated with appearance comparisons. Additionally, adjusting lighting and camera angles, and amount of time spent looking at oneself are associated with self‐objectification.